Social And Spiritual Importance of Lessons of Musical Culture - Raximov Omadjon Nurmuhammadovich; Nasritdinova Madina Nurullaevna (Zien Journals, 2021)
This article discusses the teaching of music culture in secondary schools, the sociospiritual significance of these lessons in the education of a harmoniously developed generation.
Keywords: Music Culture Lessons; Socio-Spiritual; Young Generation; General Education